2022
DOI: 10.1016/j.amepre.2021.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Obesity Prevention and Treatment Among Hispanics: A Systematic Review and Meta-Analysis

Abstract: Introduction:The rates of pediatric obesity in the U.S. are highest among Hispanics. There is no existing meta-analysis of the effects of obesity interventions among Hispanic youth. This systematic review and meta-analysis assesses the effects of obesity prevention and treatment interventions on Hispanic youth's weight status and lifestyle behaviors.Methods: PubMed, PsycINFO, and Scopus were searched between January 1, 2000 and October 30, 2020. Interventions with ≥50% Hispanic youth aged 0−18 years were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Latino youth have the highest prevalence of obesity (26%) relative to all other racial/ethnic groups (Fryar et al, 2020). Our team conducted a systematic review and metaanalysis of obesity prevention and treatment interventions among Latino youth aged 0-18 years old and found that few interventions targeting adolescents were primarily familybased despite the cultural relevance of familism (St. George et al, 2021). We also noted that only 4% of the >100 studies leveraged some form of technology (e.g., Internet, texts).…”
Section: Case Example 3: Technology Development (Sms Vp)mentioning
confidence: 99%
“…Latino youth have the highest prevalence of obesity (26%) relative to all other racial/ethnic groups (Fryar et al, 2020). Our team conducted a systematic review and metaanalysis of obesity prevention and treatment interventions among Latino youth aged 0-18 years old and found that few interventions targeting adolescents were primarily familybased despite the cultural relevance of familism (St. George et al, 2021). We also noted that only 4% of the >100 studies leveraged some form of technology (e.g., Internet, texts).…”
Section: Case Example 3: Technology Development (Sms Vp)mentioning
confidence: 99%
“…In two reviews of technology-based nutrition education (Gomes et al, 2021 ; Zarnowiecki et al, 2020 ), only one study of families with low incomes was cited. Similarly, in a meta-analysis of obesity programs for Hispanic youth (including both family- and youth-based programs), St. George et al ( 2022 ) found that only 4% of programs employed technology for content delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Given the widespread availability and accessibility of SMS text message communication, strategies that leverage this method of communication are promising for reaching and engaging adolescents at high risk. For example, Hispanic youths are disproportionately burdened by high rates of obesity (27% vs 21.5% of the general population) and subsequent T2D compared with other pediatric subgroups [4,5]. SMS text message-based interventions may be ideal for this population, as 95% of Hispanic youths report owning their own mobile phone [6], and adolescents are the highest users of SMS text message communication compared with other age groups [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%